2017
DOI: 10.1002/ppul.23659
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro ivacaftor response in cystic fibrosis patients with residual CFTR function: N‐of‐1 studies

Abstract: Summary Rationale: Ivacaftor, a cystic fibrosis transmembrane conductance regulator (CFTR) potentiator, decreases sweat chloride concentration, and improves pulmonary function in 6% of cystic fibrosis (CF) patients with specific CFTR mutations. Ivacaftor increases chloride transport in many other CFTR mutations in non-human cells, if CFTR is in the epithelium. Some CF patients have CFTR in the epithelium with residual CFTR function. The effect of ivacaftor in these patients is unknown. Methods: This was a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 49 publications
1
51
2
3
Order By: Relevance
“…VX-770 has been reported to increase the activity of some CFTR mutants and wild type CFTR channels, although its effect on WT-CFTR is variable (72,73). In our study VX-770 treatment did not elevate chloride current in non-CF hBE cells ( Supplementary Figure S2B, C) and provided little improvement in channel activity in c.3718-2477T cells (Figure 2), although it is possible that a VX-770 effect could be obscured by hyperphosphorylation of CFTR (74,75). Likewise, data from clinical trials showed only modest improvement in endpoints for patients with the splice mutation (29, kalydecohcp.com).…”
Section: Discussioncontrasting
confidence: 45%
“…VX-770 has been reported to increase the activity of some CFTR mutants and wild type CFTR channels, although its effect on WT-CFTR is variable (72,73). In our study VX-770 treatment did not elevate chloride current in non-CF hBE cells ( Supplementary Figure S2B, C) and provided little improvement in channel activity in c.3718-2477T cells (Figure 2), although it is possible that a VX-770 effect could be obscured by hyperphosphorylation of CFTR (74,75). Likewise, data from clinical trials showed only modest improvement in endpoints for patients with the splice mutation (29, kalydecohcp.com).…”
Section: Discussioncontrasting
confidence: 45%
“…Responses from intestinal organoids were also demonstrated to correlate with intestinal current measurements, reduction in sweat chloride concentration and improvement in lung function of patients after CFTR modulator therapies (Dekkers et al, 2016a;Berkers et al, 2019). In N-of-1 trial series, an increase in CFTR-dependent chloride transport in nasal epithelial cell cultures was only found in the three patients who also demonstrated a reduction in sweat chloride concentration after ivacaftor treatment (McGarry et al, 2017). Furthermore, responses in F508del-homozygous patient-derived nasal epithelial cells were correlated to improvements in ppFEV 1 and intestinal current measurements, but not with nasal potential difference after co-treatment with lumacaftor/ ivacaftor (Pranke et al, 2019).…”
Section: Continuing the Development Of Transformative Therapeutics Tomentioning
confidence: 93%
“…P67L (c.200C>T) was initially identified as a class IV mutation, supported by a milder phenotype of pancreatic sufficiency, delayed onset of symptoms, but also the potential for moderate lung disease [7]. A study by Sabusap et al [8**] [27]. The authors suggested that these "N-of-1" studies could be used to investigate the effect of CFTR modulators in PWCF with varying phenotypes and genotypes.…”
Section: Current Cftr Classification Systemmentioning
confidence: 99%